Correlation study between image features and mechanical properties of Han Chinese facial skin. (23rd August 2016) - Ma, L.; Tan, Y.; Zheng, S.; Li, J.; Jiang, C.; Chen, Z.; Wang, X.
Abstract: Objective: Mechanical properties are considered to be vital factors that influence skin physiology during ageing. Wrinkles and skin roughness are the two main features in aged skin. The purpose of this study is to characterize the relationship between facial skin mechanical properties and image features using quantitative methods. Methods: Two hundred and forty healthy male and female volunteers living in Shanghai, China (aged 20–70 years), were examined in this study. Facial images were photographed by VISIA‐CR. Wrinkle volume of middle forehead and skin roughness of upper cheek were analysed by Skin Surface Analyzer (SSA) software. Mechanical parameters at the middle forehead and upper cheek were measured using Cutometer ® MPA 580 and Reviscometer ® RVM 600. Results: Skin wrinkles and roughness increased during ageing, where men have a higher level and earlier manifestation than women. Skin mechanical parameters R2, R5, R7 and RRT were found decreased with age. Moreover, mechanical parameters including R2, R7, RRT and anisotropy showed significant correlations with wrinkle volume and/or skin roughness. Conclusion: The facial image features including wrinkle volume and skin roughness are significantly correlated with skin elasticity and anisotropy, which could well describe the skin features of Han Chinese. Résumé: Objectif: Les propriétés mécaniques sont considérées comme des facteurs essentiels qui influent sur la physiologie de la peau au cours du vieillissement. Rides et rugosité de la peau sont les deux principales caractéristiques de la peau âgée. Le but de cette étude est de caractériser la relation entre les propriétés mécaniques de la peau du visage et les caractéristiques d'images en utilisant des méthodes quantitatives. Méthodes: Deux cent quarante volontaires masculins et féminins en bonne santé vivant à Shanghai en Chine (âgés de 20‐70 ans) ont été examinés dans cette étude. Des images du visage ont été obtenues par VISIA‐CR. Le volume des rides du front milieu et la rugosité de la peau de la joue supérieure ont été analysés par le logiciel de l'analyseur de surface de la peau (SSA). Les paramètres mécaniques au niveau du front du milieu et de la joue supérieure ont été mesurés en utilisant le Cutomètre® MPA 580 et le Reviscometer ® RVM 600. Résultats: Les rides et la rugosité de la peau ont augmenté au cours du vieillissement, où les hommes ont des valeurs plus élevées et les manifestations plus tôt que les femmes. Les paramètres mécaniques R2, R5, R7 et RRT de la peau ont été trouvées diminuées avec l'âge. En outre, les paramètres mécaniques, y compris R2, R7, RRT et anisotropie ont montré des corrélations significatives avec le volume des rides et/ou la rugosité de la peau. Conclusion: Les caractéristiques de l'image du visage, y compris le volume des rides et de la rugosité de la peau sont significativement corrélées avec l'élasticité et l'anisotropie de la peau, qui pourrait bien décrire les caractéristiques de la peau des Chinois Han.